A method to estimate active-layer thickness on the basis of correlations between terrain and climatic parameters as measured in northern Quebec - Gray, James T.; Pilon, Jean; Poitevin, Jean (Canadian Geotechnical Journal, 1988)
Field studies recently conducted on the west coast of Ungava Bay, in the southern part of the continuous permafrost zone, have permitted the establishment of the pattern of active-layer development for six different geomorphological and vegetational terrain types. All study sites were situated on horizontal surfaces free from local topographic influences, to permit the explanation of thaw progression, in terms of the earth materials, moisture content, and vegetation cover characterizing each terrain type. Thermal properties for organic and mineral soil, and for bedrock, were calculated from field data on texture, bulk density, and moisture content of the earth materials at the sites, and were used to explain thaw-layer development for each terrain type. A linear regression was established for each group of sites between the logarithmic transformation of thaw penetration and an atmospheric thawing index obtained through interpolations of air temperature data from the two closest meteorological stations—Kuujjuaq (Fort Chimo) and Koartaq (Cape Hope's Advance). This regression was then used to estimate the total thickness of the active layer at the end of the thaw season for each terrain type, and to assess probable variations in active-layer depths in the region over a 20 year time period. Probable spatial variations of active layers for extreme climatic variations in the Ungava Peninsula are also briefly presented. Key words: active layer, permafrost, thermal, thaw penetration, terrain analyses, Ungava.